New Types of Libraries in the Republic of Tyva - I. V. Podik (Библиосфера, 2022)
The article focuses on the issue of the mass appearance of the “public”, “folk” and street libraries in the Republic of Tyva. The author gives the historical experience of creating such libraries in the region, concentrates herself on their future and compares it with the open of modern “public” and “folk” libraries. The aim of the study is to conceptualize this phenomenon as the process of the transformation of the “public” libraries, or as a new form of the library space organization in the region. Basing on the research results there arises a question, related to the need for creation and existence of such libraries. The conclusion is as follows. It is possible to change the library services organization in public libraries, via, e.g., the creation of reading rooms with free access to the certain parts of library collection without registration as a reader, the opening of outof-station service points in convenient places for people, the organization of bookcrossing. For further investigating the demand for the “public’, ‘folk” and street libraries it is necessary to conduct a population survey, as well as to study the quality of the library and information services of the libraries of the Republic of Tyva.